A critical study on the Sedition Act 1948 in Malaysia / Nur Hidayah Saidi … [et al.] - Saidi, Nur Hidayah; Bustaman, Nurul Liyana; Shafit, Nornadia Shafleena; Abdullah Azmi, Syaza Izzati; Yusof, Wan Nurul Afiqah (2010)
The law of Sedition in Malaysia has come into existence before Malaysia achieves an independent. The law of Sedition 1948 has been applied in Malaysia since the year of 1948. Since this law is pre Merdeka law, the question arises as whether this law is relevant to be applied in current situation. In order to prosecute the person is liable under this law, the intention is immaterial. It is sufficient the person is committing a seditious tendency. Since it is a criminal offence, this sedition law has deemed to entrenched the principle of criminal offence whereby in order to prosecute an offender under criminal law, there must be fulfilled two elements which are actus reus and mens rea. Sedition law also has deemed to envisage the right of freedom of speech provided in Federal Constitution which is supreme law of the land. Therefore, freedom of speech is actually not an absolute freedom. It is the discretion of the Parliament itself. This freedom of speech itself restrict by a few written law and one of the example is the Sedition Law 1948 itself. This project paper will makes a critical study on the Sedition Act 1948.